Analysis of Media Coverage on Breastfeeding Policy in Washington State. (February 2018) - DeMarchis, Alessandra; Ritter, Gaelen; Otten, Jennifer; Johnson, Donna
Background: Media coverage and message framing about breastfeeding polices can influence important policy decisions in institutional and governmental settings. Research aim: This study aimed to describe the media coverage of breastfeeding policies and the message frames that are found in print newspapers and web-only news publications in Washington State between 2000 and 2014. Methods: For this retrospective media analysis study, 131 news articles published from January 2000 through June 2014 in Washington State that specifically discussed breastfeeding policy were identified, coded, and analyzed to explore the content of the sample and examine how arguments supporting or opposing breastfeeding policy were framed. The coding scheme was developed cooperatively and found to be reliable across coders. Results: The number of articles published each year about breastfeeding policy grew overall between 2000 and 2014 and peaked during periods of specific policy development. Seventy-four articles had a neutral tone, 49 supported breastfeeding policy, and 4 were in opposition. Nine distinct supporting frames and six distinct opposing frames were identified. Common supporting frames were health benefits of breastfeeding and the need for policies because of challenges of breastfeeding in public. The most common opposing frame was indecency of breastfeeding in public. Conclusion: There is limited but growing media coverage of breastfeeding policies. For the most part, coverage is supportive of the need for policies. Breastfeeding advocates can apply information about media message frames to craft effective policy development strategies that counteract negative perceptions and promote the benefits of breastfeeding policies.